Analisis Celebrity Endorsment terhadap Keputusan Pembelian Pelanggan Online Shop Shopee dengan Minat Beli sebagai Variabel Intervening - Firmansyah, Denny; Haryani; Safrina, Emi; Diah, Muhammad (Jurnal Informatika Ekonomi Bisnis, 2023)
The purpose of this study was to determine the effect of celebrity endorsement on purchasing decisions with purchase intention as an intervening variable. This study used a sample of 120 online shop Shopee customers in Medan City. The sampling technique is purposive sampling where only customers who have shopped at the Shopee online shop and have watched Shopee endorsement ads can be sampled. The model used with path analysis and processed with Amos 24.0. The results of the study found that celebrity endorsement had a positive and significant effect on purchase intention, celebrity endorsement and purchase intention had a positive and significant effect on purchasing decisions, buying interest mediated the effect of celebrity endorsement on purchasing decisions by partial mediation.